Implementation of a centralized, web-based surveillance for healthcare associated infections among residents of long-term care facilities in Italy - Costanza Vicentini; Antonino Russotto; Stefano Bazzolo; Edoardo Rolfini; Valentina Blengini; Dario Gamba; Antonella Agodi; Martina Barchitta; Stefania Bellio; Elisa Fabbri; Silvia Forni; Enrico Ricchizzi; et al. (Elsevier, 2023)
Objective: The Italian National Action Plan to contrast AMR identified among its objectives the development and implementation of a national Healthcare-Associated Infection (HAI) surveillance system based on European Centre for Disease Prevention and Control (ECDC) indications, through point prevalence surveys (PPS) of HAIs and antibiotic use in acute-care hospitals and long-term care facilities (LTCFs). We aimed to assess feasibility and appropriateness of proposed tools for a national surveillance system of HAIs and antibiotic use in LTCFs. Study design: Point prevalence survey. Methods: A pilot PPS was conducted between May-June 2022, among 15 LTCFs of 7 Italian regions. Data were collected in a single day in each LTCF, at the LTCF, ward, and resident levels, using a web-based data collection tool developed ad hoc. Data collector teams of each facility were invited to complete a questionnaire investigating opinions on the proposed tools. Results: Among 1025 included residents, the prevalence of residents with at least one HAI was 2.5% (95% CI 1.7%-3.7%) considering all HAIs and 2.2% (95% CI 1.3%-3%) without considering SARS-CoV-2 infections. The prevalence of antimicrobial use was 3% (95% CI 0.2%-4.3%). Overall, most respondents were satisfied with the web-based software, training and protocol, even though some difficulties were reported. Conclusions: A national surveillance network was established, which will facilitate future surveillance efforts. Further studies are necessary to evaluate the impact of the pandemic on HAI transmission and antibiotic use in LTCFs.